2015
DOI: 10.1681/asn.2013080864
|View full text |Cite
|
Sign up to set email alerts
|

Scattered Deletion of PKD1 in Kidneys Causes a Cystic Snowball Effect and Recapitulates Polycystic Kidney Disease

Abstract: In total, 1 in 1000 individuals carries a germline mutation in the PKD1 or PKD2 gene, which leads to autosomal dominant polycystic kidney disease (ADPKD). Cysts can form early in life and progressively increase in number and size during adulthood. Extensive research has led to the presumption that somatic inactivation of the remaining allele initiates the formation of cysts, and the progression is further accelerated by renal injury. However, this hypothesis is primarily on the basis of animal studies, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 44 publications
3
56
0
Order By: Relevance
“…Several studies have reported that many promising drugs showed potential therapeutic effects for ADP-KD in a large number of preclinical and clinical trials (1,7,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). However, some of those in clinical trials -these promising drugs included mTOR inhibitors (55,56), somatostatin analogs (57,58), ACEI/ ARB (59,60), and tyrosine kinase inhibitor (61) -did not prevent the decline of EGFR in ADPKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that many promising drugs showed potential therapeutic effects for ADP-KD in a large number of preclinical and clinical trials (1,7,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). However, some of those in clinical trials -these promising drugs included mTOR inhibitors (55,56), somatostatin analogs (57,58), ACEI/ ARB (59,60), and tyrosine kinase inhibitor (61) -did not prevent the decline of EGFR in ADPKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although preclinical studies have reported that rapamycin is an effective treatment for ADPKD in animal models , clinical trials of rapamycin treatment for ADPKD patients have been less successful . These poor clinical results might be due to insufficient rapamycin . To verify this possibility in a cohort study in vivo , we treated Vil ‐Cre; Pkd2 f3/f3 mice using three additional rapamycin protocols (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although this may explain some of the focal nature of cyst formation in ADPKD, other factors have been shown to influence disease progression and severity. On a cellular level, these include: the developmental timing of PKD1 inactivation (45, 46); reduction in functional PC1 dosage (38, 47, 48); differences in sensitivity to PC1 dosage (48); and the proximity effect, where a cystic cell or nephron creates a “snowball effect” triggering cyst development in neighboring cells or nephrons (49). …”
Section: Pathophysiology and Translational Implicationsmentioning
confidence: 99%